2009
DOI: 10.1111/j.1365-2222.2009.03334.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin and lovastatin inhibit granulocyte macrophage–colony stimulating factor‐stimulated human eosinophil adhesion to inter‐cellular adhesion molecule‐1 under flow conditions

Abstract: Inhibition of eosinophil adhesion to ICAM-1 by fluvastatin and lovastatin under physiological shear stress represent novel actions by these drugs that may inform the development of anti-inflammatory therapy for allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 41 publications
2
20
0
1
Order By: Relevance
“…Although fluvastatin exerted antiinflammatory effects (IL-8) in both cell lines, our data show that this was not mediated by the induction of A20 (mRNA), clearly confirming the sscMap prediction. In asthma, fluvastatin inhibits eosinophil adhesion to ICAM-1 (39) and fibroblast proliferation (40). Using similar concentrations, we did not observe any reduced proliferation.…”
Section: Discussionmentioning
confidence: 63%
“…Although fluvastatin exerted antiinflammatory effects (IL-8) in both cell lines, our data show that this was not mediated by the induction of A20 (mRNA), clearly confirming the sscMap prediction. In asthma, fluvastatin inhibits eosinophil adhesion to ICAM-1 (39) and fibroblast proliferation (40). Using similar concentrations, we did not observe any reduced proliferation.…”
Section: Discussionmentioning
confidence: 63%
“…There are also reports that human eosinophils can process and present antigen to activate specific T cells, (20) but, again, it remains to be established how widespread is such ability in different individuals and for different antigens. Despite the evidence that eosinophils have the potential to act as APC to drive Th cell responses and thereby propagate inflammation, (21,22) other findings have suggested that this is limited to super-antigens and peptides, rather than proteins that require processing. (11,16) The effects of Th activation are critically dependent on the subset(s) that respond, and the associated cytokines they produce, but it is not known whether eosinophil antigen presentation preferentially supports responses by any particular Th type.…”
Section: Introductionmentioning
confidence: 99%
“…(22) Briefly, eosinophils and CD4 + Th cells were removed from co-culture, washed and saturating quantities of primary antibodies or specific isotype controls were added to the cells and incubated for 40 min at 4 0 C in the dark, washed and fixed.…”
Section: Immunostaining and Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Fluvastatin and lovastatin inhibited the adhesion of human eosinophils to recombinant human intercellular adhesion molecule-1, and this effect was reversed by the addition of mevalonate [43] . In addition, pravastatin and fluvastatin reduced the expression of intercellular adhesion molecule-1 and the release of TNF-α, IFN-γ and IL-12 from cultured human peripheral blood mononuclear cells [43] . In recent years, it has been suggested that the accumulation of eosinophils in asthma could be due to their prolonged survival and defective apoptosis [44,45] .…”
Section: Pharmacological Targets Of Statins In Asthmamentioning
confidence: 99%